EFFICIENCY ANALYSIS OF FIRE TUBE BOILER TYPE AT REFINERY UTILITY UNIT CENTER FOR OIL AND GAS HUMAN RESOURCES DEVELOPME - Aliyah Shahab; Sulton Amna (Jurnal Cakrawala Ilmiah, 2023)
The boilers are covered vessels that are used to produce steam. The steam produced from this boiler generally comes from burning processes that use both gas, liquid, and solid fuel. The problems that often occur in the field are boiler machines that are not efficient properly When working systems or operating processes in the field. The efficiency of the boiler is a sum that shows a connection of supply energy getting into the boiler with the overall energy generated by the boiler. From boiler efficiency calculations using direct method is the method used to measure efficiency by measuring the output of steam relative to the heat generated by the fuel burning, this method is also known as thermal boiler efficiency and is obtained efficiency of 48,15%. While the indirect method (indirect method) is a way of measuring the efficiency of the boiler by measuring the magnitude of the unbeneficial heat (heat lass), it is most effective in the effort to find boiler energy savings potential based on heat scales and acquired boiler efficiency by 68,22%.